(untitled) (Research, Society and Development, 2022)
This study aimed to histologically evaluate the pharmacological activity of meloxicam, COX-2 inhibitor, on liver function in arthritic rats. Meloxicam is a non-steroidal anti-inflammatory drug (NSAID), COX-2 inhibitor, generally prescribed in the area of rheumatology. Thus, 18 Wistar rats were divided into 3 groups with 6 animals each: G1 (Negative Control), G2 (Arthritis induced with Zymosan [Zy]), G3 (Arthritis induced with Zymosan [Zy] and treated with meloxicam). The G3 treatment started on the 21st day after induction. The animals were sacrificed, by overdose of Ketamine/Xylazine, seven, 14 and 21 days after the beginning of the meloxicam treatment. Liver samples were collected from the animals, fixed in Millonig buffer containing 10% formaldehyde and processed for conventional histological analysis. G1 animals showed absence of inflammation and degeneration of hepatocytes. In the G2 group, a slight cytoplasmic alteration was observed at seven and 14 days. At 21 days, intense cytoplasmic and nuclear disorganization was detected, accompanied by cell necrosis. In G3, large spacing between sinusoid capillaries was detected. In some 14-day-old animals, amyloidosis was observed, with the presence of a large number of vacuolated hepatocytes involved in an amorphous mass of necrotic cells. Most of the hepatocyte nuclei had compacted chromatin, evidencing cellular degeneration. Meloxican, used as an anti-inflammatory in the synovial region, showed that, in addition to its beneficial effects for the treatment of rheumatological diseases, it is capable of, when administered orally, promoting a high level of liver damage.